2020
DOI: 10.3390/nu12102985
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Factors and Supplements Influencing Prostate-Specific Antigen (PSA) Concentrations in Men with Prostate Cancer and Increased Cancer Risk: An Evidence Analysis Review Based on Randomized Controlled Trials

Abstract: The quest for dietary patterns and supplements efficient in down-regulating prostate-specific antigen (PSA) concentrations among men with prostate cancer (PCa) or increased PCa risk has been long. Several antioxidants, including lycopene, selenium, curcumin, coenzyme Q10, phytoestrogens (including isoflavones and flavonoids), green tea catechins, cernitin, vitamins (C, E, D) and multivitamins, medicinal mushrooms (Ganoderma lucidum), fruit extracts (saw palmetto, cranberries, pomegranate), walnuts and fatty ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 224 publications
(264 reference statements)
0
20
1
Order By: Relevance
“…More recent studies highlighted that low selenium concentration in plasma was associated with a 4- to 5-fold increased risk of prostate cancer, in a case-control study that included 318 patients [ 78 ]. However, this result is in contrast both with evidence from the previous Sel enium and vitamin E C ancer prevention T rial (SELECT) study [ 75 , 79 , 80 ] and with the results of a 2020 review of randomized controlled trials [ 81 ]. Some authors have suggested that divergent results could be primary due to the different specific cancer type considered, as well as to the selenium form and to the initial plasma selenium levels of the participants in the trials [ 82 ].…”
Section: Cancercontrasting
confidence: 64%
“…More recent studies highlighted that low selenium concentration in plasma was associated with a 4- to 5-fold increased risk of prostate cancer, in a case-control study that included 318 patients [ 78 ]. However, this result is in contrast both with evidence from the previous Sel enium and vitamin E C ancer prevention T rial (SELECT) study [ 75 , 79 , 80 ] and with the results of a 2020 review of randomized controlled trials [ 81 ]. Some authors have suggested that divergent results could be primary due to the different specific cancer type considered, as well as to the selenium form and to the initial plasma selenium levels of the participants in the trials [ 82 ].…”
Section: Cancercontrasting
confidence: 64%
“…S. lycopersicum fruits are typically composed of 94.5% water, 3.89% carbohydrates (1.2% of total dietary fiber and 2.63% of sugars), 0.88% protein and 0.2% total lipid (fat), while other nutrients and phytochemicals include minerals (e.g., 237 mg potassium, 24 mg phosphorus, 11 mg magnesium, 10 mg calcium), vitamins (e.g., 13.7 mg vitamin C, 0.12 mg γ-tocopherol, 0.6 mg niacin), and tetraterpenes (e.g., 449 μg β-carotene, 101 μg α-carotene, and 2570 μg lycopene, collectively known as carotenoids) [ 83 ] ( Table 2 ). Lycopene has been widely studied in relation to prostate dysfunctions, including BPH and prostate cancer [ 136 , 137 , 138 ].…”
Section: Medicinal Plants Widely Used In the Treatment Of Bphmentioning
confidence: 99%
“…Regarding the relationship between isoflavones and prostate diseases, research has reported that isoflavones exert a preventive effect on prostate carcinogenesis due to their phytoestrogen action [ 16 ]. In addition, many investigators have paid special attention to the anti-cancer effects of isoflavones in prostate cancer [ 67 , 68 , 69 ]. In contrast to prostate cancer, studies on the pharmacological effects of isoflavones on BPH are smaller.…”
Section: Management Of Benign Prostate Hyperplasia With Polyphenolmentioning
confidence: 99%
“…Interestingly, this study also showed that there were no significant differences in plasma levels of luteinizing hormone (LH) or the estradiol and testicular levels of testicular steroidogenic acute regulatory peptide between the phytoestrogen-rich included isoflavones and the phytoestrogen-free Regarding the relationship between isoflavones and prostate diseases, research has reported that isoflavones exert a preventive effect on prostate carcinogenesis due to their phytoestrogen action [16]. In addition, many investigators have paid special attention to the anti-cancer effects of isoflavones in prostate cancer [67][68][69]. In contrast to prostate cancer, studies on the pharmacological effects of isoflavones on BPH are smaller.…”
Section: Isoflavonesmentioning
confidence: 99%